Assessing The Impact Of The Adoption Of The International Financial Reporting Standard (IFRS) On Financial Reporting Practices: Selected Commercial Banks In Nigeria - Iheonkhan Iyere Samuel; Sulaiman T. H (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
A huge number of stakeholders rely on the bank's financial statements. Such financial accounts must be of the highest caliber, particularly in light of the emergence of globalization. The International Financial Reporting Standards (IFRSs) were created to provide high-quality financial reporting in addition to universal standards. Over the past 10 years, Nigerian banks' financial statements have been called into question to the point where several of these banks failed. The purpose of this study is to investigate how IFRSs have affected Nigerian banks' financial statements quality, with a focus on the relevance, comparability, and clarity of their goals. The study's conclusions were reached using a case study methodology. There is a survey involving various stakeholders, both internal and external, through the use of a questionnaire. To analyze the data, the Chi-Square method was used. The X2-calculated value of 14.96 is more than the X2-critical/table value of 5.99 at 0.05 LOS, indicating a substantial association between the adoption of IFRS and the comparability objectives of Nigerian banks, according to the results. Further research revealed that the adoption of IFRS has a significant impact on relevancy quality, as the X2-calculated value of 14.0 is higher at 0.05 LOS than the X2-critical/table value at 5.99. The implementation of IFRS has also been proven to have a considerable impact on Nigerian banks' clarity objectives, as evidenced by the fact that the X2-calculated value of 25.4 is more than the X2-critical/table value of 5.99 at 0.05 LOS. It was determined that the implementation of IFRS has an important influence on the standard of Nigerian banks' financial statements. Enforcing the use of IFRS in the preparation and publication of financial statements is advised. If the accounts meet the standards' requirements, the auditors should state so